Synthesis of Enantiopure Sulfoxides by Concurrent Photocatalytic Oxidation and Biocatalytic Reduction. (4th March 2022) - Bierbaumer, Sarah; Schmermund, Luca; List, Alexander; Winkler, Christoph K.; Glueck, Silvia M.; Kroutil, Wolfgang
Abstract: The concurrent operation of chemical and biocatalytic reactions in one pot is still a challenging task, and, in particular for chemical photocatalysts, examples besides simple cofactor recycling systems are rare. However, especially due to the complementary chemistry that the two fields of catalysis promote, their combination in one pot has the potential to unlock intriguing, unprecedented overall reactivities. Herein we demonstrate a concurrent biocatalytic reduction and photocatalytic oxidation process. Specifically, the enantioselective biocatalytic sulfoxide reduction using ( S )‐selective methionine sulfoxide reductases was coupled to an unselective light‐dependent sulfoxidation. Protochlorophyllide was established as a new green photocatalyst for the sulfoxidation. Overall, a cyclic deracemization process to produce nonracemic sulfoxides was achieved and the target compounds were obtained with excellent conversions (up to 91 %) and superb optical purity (>99 % ee ). Abstract : The power of biocatalysis and photocatalysis was combined in one pot for a concurrent reduction–oxidation sequence to gain access to enantiopure sulfoxides. In a cyclic deracemization process the enantioselective biocatalytic reduction is followed by a non‐stereoselective light‐dependent oxidation to yield the desired target compounds in >99 % ee. rac‐ sulfoxides carrying various substituents on the aromatic ring were well accepted by the system.